The Influence of Soft Skills, Work Environment, and Job Satisfaction on the Performance of Contract Employees at the Department of Culture, Gianyar Regency - Dewa Ayu Cahya Oktafiani; Putu Gede Denny Herlambang; Octavianus Sumardana Pratama (Countable (Contemporary Business and Sustainability Science), 2025)
This study aimed to investigate the significant simultaneous and regional  effects of soft skills, working conditions, and job satisfaction on the performance of  contractors in the Cultural Office of Gianyar Regency. Saturated sampling was used to  collect a sample of 115 contractors. Data sources included both primary and secondary  sources, with both quantitative and qualitative characteristics. Data collection methods  included surveillance, questions and answers, questionnaires, and sampling surveys.  Data analysis used multiple linear regression. The results showed that soft skills, working  conditions, and job satisfaction had a significant simultaneous and partial effect on the  performance of contractors in the Cultural Office of Gianyar Regency.